Efficacy of staplers in comparison with conventional (Hand-Sewn) anastomosis in gastrointestinal surgery – A prospective and randomized study - Arunkumar D; Meghan GS; Shivasharan HN; Neeta PN (Asian Journal of Medical Sciences, 2024)
Background: Gastrointestinal anastomosis is a regularly carried out surgical technique to set up communication between two distant portions of the intestine since the era of Sushruta. There exist different methods of intestinal anastomosis. The newer techniques are Stapling devices over to conventional hand-sewn method of anastomosis. It is proved that a key to a successful anastomosis is accurate anastomosis of two viable ends of the bowel maintaining good vascularity and less tension. Due to consistency, stapler’s can be used at difficult locations. Aims and Objectives: The objective of present study was to compare the outcome of hand-sewn versus stapler anastomosis in elective gastrointestinal surgeries. Materials and Methods: We conducted a prospective and randomized study including 30 study participants each in stapler’s method and hand-sewn method at surgery outpatient department of Kempegouda Institute of Medical Sciences Hospital and Research Center. Results: Stapling procedure took less days to get restored, less time to return of bowel sounds, shorter duration of hospital stays, and less time to resume for oral feeds compared to hand-sewn method and which were statistically significant (P<0.05). Complications such as anastomotic leaks accounted for 3.3% in stapler group and 13.3% in hand-sewn anastomosis, which was not significant statistically. Conclusion: We concluded that time for anastomosis during the procedure, restoration of the gastrointestinal function, oral feeding resumption, and post-operative hospital stay took significantly less time in stapling technique than hand-sewn anastomosis and the staplers looked technically easy compared to hand-sewn method. Complications related to procedure did not show significant differences which helped us to conclude that one can use staplers with similar safety and accuracy as hand suturing method.